Sedimentary environment and the controlling factors of organic-rich rocks in the Lucaogou Formation of the Jimusar Sag, Junggar Basin, NW China - Chang-Sheng Qu (KeAi Communications Co., Ltd., 2019)
Abstract The Lucaogou Formation in the Jimusar Sag of the eastern Junggar Basin is an important sedimentary stratum accumulating huge amounts of lacustrine tight oil in China, where organic-rich rocks are commonly observed. Focusing on the Lucaogou Formation, a precise analysis of the inorganic and organic petrology and the inorganic geochemistry characteristics was conducted. The paleoclimate and paleoenvironment during sedimentation of the Lucaogou Formation were established, and the key factors that were controlling the accumulation of organic matter during this time were identified. The results of this study suggest that during the sedimentation of the Lucaogou Formation, the paleoclimate periodically changed from a humid environment to an arid environment. As a result, the salinity of the water and the redox environment fluctuated. During the sedimentation period, the lake showed sufficient nutrient supplies and a high primary productivity. The interval studies in the Lucaogou Formation were divided into five sedimentary cycles, where the first, second, and fifth sedimentary cycles consisted of cyclical paleoclimate fluctuations varied from a humid environment to an arid environment and shifted back to a humid environment with levels of salinity from low to high and decreased again. The third and fourth cycles have cyclical fluctuations from a humid to an arid environment and corresponding salinity variation between low and high levels. During the period when organic-rich rocks in the Lucaogou Formation deposited in the Jimusar Sag, the paleoclimate and the water body were suitable for lower aquatic organisms to flourish. As a result, its paleoproductivity was high, especially during the early period of each cycle. A quiet deep water body is likely to form an anoxic environment at the bottom and is also good for accumulation and preservation of organisms. Fine-grained sediments were accumulated at a low deposition rate, with a low dilution of organic matter. Therefore, high paleoproductivity provided a sufficient volume of organisms in the studied area in a quiet deep water body with an anoxic environment and these were the key factors controlling formation of organic-rich rocks.